A STUDY CONCERNING THE EFFICIENCY OF THE SPORTS AND RELAY RACES IN MASTERING THE TECHNIQUE OF THE HANDBALL GAME IN 5TH GRADE STUDENTS - Juravle Bogdan Ioan; Leuciuc Florin Valentin (Editura Univeristatii "Stefan cel Mare" din Suceava, 2020)
Handball is a sport practiced with speed, the contestants have to work as a team in order to achieve victories. In relay races and dynamic sports, a good cooperation between the members of the team is needed in order to win. Through sports and relay races they develop their qualities and dynamic abilities and can form themselves into social groups. The sport means a free experience and is practiced out of pleasure and comes from the desire of overcoming the others, of getting over an obstacle, of being first and of winning, offering confidence in their own power. The sports are used in all educational levels. Using dynamic sports in the Physical Education class increases the efficiency and ensures a better training through the students' conscient and active participation, contributes to the improvement of their behavior and to the installment of a climate of order and discipline. The sport distinguishes itself through group activity, which implies cooperation, team work and assuming responsibilities. In some situations of the sport, favorable or unfavorable conditions can appear, conditions which lead to the exteriorization of students' emotional states. In a sport there can appear new and unforeseen situations, so the participants must react promptly and use the best solutions.